The Relevance of Different Oxygen Reduction Pathways of La0.8Sr0.2MnO3 (LSM) Thin Film Model Electrodes. Issue 3 (1st January 2015) - Huber, T. M.; Kubicek, M.; Opitz, A. K.; Fleig, J.
Abstract : Sr-doped lanthanum manganite (LSM) is a widely used cathode material in solid oxide fuel cells (SOFC). Despite being a poor ion conductor, LSM electrodes can reduce oxygen via two pathways: a "3PB surface path" which includes surface diffusion of oxygen species and oxide ion incorporation at the three phase boundary (3PB), and a "bulk path" based on oxygen diffusion in LSM. In this work, the kinetics of both paths and their dependence on temperature and electrode geometry is investigated by impedance spectroscopy on micropatterned LSM thin film electrodes. Differently shaped and sized macroscopic and microscopic LSM electrodes as well as LSM electrodes with oxygen blocking Pt capping layers are employed to identify two parallel reaction pathways of oxygen reduction. On circular microelectrodes the 3PB surface path carries most of the current in the lower temperature region (below ca. 700°C), while at high temperatures (above ca. 700°C) the bulk path is dominating. The significance of each reduction path also depends on the microstructure of the columnar LSM films which can be changed by varying pulsed laser deposition (PLD) parameters or by annealing. Moreover, relevance of a pseudo-3PB path across edges of the LSM electrodes is discussed.